Body Composition Is Not Related to Structural or Vascular Brain Changes - Croll, Pauline H.; Bos, Daniel; Ikram, Mohammad Arfan; Rivadeneira, Fernando; Voortman, Trudy; Vernooij, Meike W. (Frontiers in Neurology, 2019)
Background: It is known that obesity [measured with body mass index (BMI)] relates to brain structure and markers of cerebral small vessel disease (CSVD). However, BMI may not adequately represent body composition. Furthermore, whether those cross-sectional associations hold longitudinally remains uncertain. Methods: Three thousand six hundred and fourty-eight participants underwent baseline (2006–2014) dual-energy X-ray absorptiometry (DXA)-scan to obtain detailed measures of body composition and a magnetic resonance imaging (MRI) scan to assess brain structure. One thousand eight hundred and fourty-four participants underwent a second MRI-scan at follow-up (2010–2017; median follow-up: 5.5 years). To assess cross-sectional and longitudinal associations (measures of change have been calculated) between body composition [BMI, fat mass index (FMI), fat-free mass index (FFMI)], and brain tissue volume (gray matter, white matter, hippocampus), white matter microstructure [fractional anisotropy (FA), mean diffusivity (MD)], and CSVD markers (white matter hyperintensity volume, lacunes, microbleeds) we used multivariable linear and logistic regression models. Results: A higher BMI and FMI were cross-sectionally associated with smaller white matter volumes (difference in Z-score per SD higher BMI: −0.064 [95% CI: −0.094, −0.035]) and FMI: −0.067 [95% CI: −0.099, −0.034], higher FA and MD. A higher FFMI was associated larger gray matter volume (difference: 0.060 [95% CI: 0.018, 0.101]). There was no statistically significant or clinically relevant association between body composition and brain changes. Conclusions: Body composition, distinguishing between fat mass and fat-free mass, does not directly influence changes in brain tissue volume, white matter integrity and markers of CSVD. Cross-sectional associations between body composition and brain tissue volume likely reflect cumulative risk or shared etiology.